2014
DOI: 10.1371/journal.pone.0101289
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Risk Profiles Associated with Chronic Complications in Overweight and Obese Type 2 Diabetes Patients in South China

Abstract: BackgroundType 2 diabetes is often accompanied by altered cardiometabolic risk profiles, including abdominal obesity, hypertension, and dyslipidaemia. The association of altered cardiometabolic risk profiles with chronic complications of diabetes is not well investigated.MethodsWe recruited 2954 type 2 diabetes patients with a body mass index ≥25 kg/m2 who visited the diabetes clinics of 62 hospitals in 21 cities in Guangdong province of China from August 2011 to March 2012. Demographic characteristics, person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…[4][5][6][7][8]10,19,21,22,24,28,30,34,[38][39][40][42][43][44][47][48][49][50][51][52][53] 69 This is consistent with other genome-wide association studies in Caucasian and Mexican-American patients. 70,71 As the relationship between genetic polymorphisms and diabetic retinopathy is still a new and emerging field, some studies have demonstrated new associations between single nucleotide polymorphisms, but these studies have not yet been replicable.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…[4][5][6][7][8]10,19,21,22,24,28,30,34,[38][39][40][42][43][44][47][48][49][50][51][52][53] 69 This is consistent with other genome-wide association studies in Caucasian and Mexican-American patients. 70,71 As the relationship between genetic polymorphisms and diabetic retinopathy is still a new and emerging field, some studies have demonstrated new associations between single nucleotide polymorphisms, but these studies have not yet been replicable.…”
supporting
confidence: 89%
“…Likewise, in a large-scale study of 2535 patients with type 2 DM, retinopathy was not significantly associated with triglyceride or high-density lipoprotein (HDL) cholesterol levels after adjustment of confounding factors. 45 In contrast, Cheng at al 4 found that in overweight type 2 DM patients, elevated triacylglycerol levels were significantly associated with diabetic retinopathy (OR=1.29; 95% CI, 1.05-1.58; P<0.05).…”
Section: Hyperlipidaemiamentioning
confidence: 91%
See 2 more Smart Citations
“…Many persons with T2DM are overweight, insulin resistant and also have dyslipidaemia and hypertension [41][42][43][44][45][46][47][48][49]. Therefore, medical nutrition therapy for T2DM should emphasize lifestyle strategies, to reduce hyperglycemia, dyslipidemia, and blood pressure [50] that result in reduced energy intake and increased energy expenditure through physical activity.…”
Section: Diet and Insulinmentioning
confidence: 99%